A bending cell for small batches - Guimarães, Rui J. (2009)
This article presents the study that is done for the conception of an automated bending cell devoted to the processing of parts in small batches, gathering the real necessities of potential customers. Joining the maximum of possible information, on the present cells, is has been able to conceive an automated bending cell devoted to the bending of parts, with dif-ferent form, weight, thickness, etc., in small batches. To be able to reach the proposed objec-tives, the cell is equipped with auxiliary systems, such as ATC (Automatic Tool Change) allied to a tool warehouse, AGC (Automatic Gripper Change) with three different grippers, a repo-sition station, and a dedicated 7th axis in the press brake designed to dock a standard 6 axes robot, that provide to cell a sufficient grade of autonomy. Allied with the idea of creating a cell for small batches, is introduced the target of getting this cell at lower price as possible. Thus the cell acquires an extended application range very important for potential customers. To get real perception of the money saving when working with this automated bending cell comparisons between Man work times vs. machine work times in production of small batches have been made.